Ensino de matemática como ferramenta para inclusão de crianças autistas no contexto escolar - Peres, Carlos Eduardo de Araújo Rodrigues (2023)
This study promotes the investigation of the effectiveness of some mathematical activities applied to children diagnosed with autism spectrum disorder (ASD). In a bibliographic survey on the subject, it was observed the low occurrence of material that explores this subject. Therefore, we briefly discuss autism and the relationships established in the face of teaching mathematics to the public with this condition. In addition, the Mathematical Skills Registration and Evaluation Protocol (PRAHM) is presented, as well as its characteristics and possibilities of application. Based on the evaluation provided by this instrument and based on some theoretical assumptions (construction of student autonomy, approximation between Mathematics and daily life), mathematical trainings were selected that could contribute to the learning of some students with ASD in the city of Itumbiara-GO. Making use of a case study, the observations and considerations regarding the application of four activities named: a) Memory game of geometric shapes; b) Mount your plate; c) Minimarket; d) Board game of geometric shapes. In addition to the report of the experiences, several methodological guidelines are provided regarding these trainings, as well as material from some of them is made available for future applications and/or improvements.